Bacillus subtilis ER-08, a multifunctional plant growth-promoting rhizobacterium, promotes the growth of fenugreek (Trigonella foenum-graecum L.) plants under salt and drought stress - Patel, Margi; Islam, Shaikhul; Husain, Fohad Mabood; Yadav, Virendra Kumar; Park, Hyun-Kyung; Yadav, Krishna Kumar; Bagatharia, Snehal; Joshi, Madhvi; Jeon, Byong-Hun; Patel, Ashish (Frontiers in Microbiology, 2023)
Introduction Sustainable agriculture and meeting the world's food needs face considerable obstacles from abiotic stresses such as soil salinity and drought. This critical issue was addressed by our current study, which sought to uncover multi-trait bioinoculants from hostile ecosystems that could help mitigate salinity and drought stresses at the same time. Methods The Bacillus subtilis ER-08 (BST) strain was isolated from the halotolerant plant Fagonia cretica which was collected from the Little Rann of Kachchh, India. Various biochemical and molecular approaches were applied for the detailed characterization of the BST isolate. Results and discussion The BST isolate demonstrated notable plant growth-promoting qualities. Fenugreek seed biopriming was performed using the BST isolate. The effect of BST seed treatment on fenugreek developmental indices as well as abiotic alleviation was examined under greenhouse conditions. The BST produced 83.7 g ml−1 gibberellins (GA3) and 176.1 g ml−1 indole-3 acetic acid. Moreover, hydrogen cyanide, siderophore, exopolysaccharides (EPS), ammonia, cellulase, protease, pectinase, and chitinase were also produced by the BST strain. Interestingly, 52% of Fusarium oxysporum mycelial growth was suppressed by the BST isolate under in vitro conditions. Furthermore, BST isolates functioned well under several abiotic stress conditions, for instance, salinity (4 and 6 ds m−1), pH (5, 7, and 9), drought (PEG6000 at 10%, 20%, and 30%), and temperature (25°C, 35°C, 37°C, and 55°C). This study indicates that the BST strain might serve as an effective bio-inoculant for minimizing the detrimental effects of abiotic stresses.